2005
DOI: 10.1159/000081733
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Hepatitis C Virus by G-1 Beads in Sera from Patients with Chronic Hepatitis C

Abstract: Recently, a new method of extracorporeal granulocyte depletion apheresis has been developed to treat inflammatory systemic diseases using an Adacolumn (Japan Immunoresearch Laboratories, Takasaki, Japan) that is filled with acetate cellulose beads (G-1 beads) to adsorb the granulocytes. We examined whether hepatitis C virus (HCV) is adsorbed after incubation of the Adacolumn with the sera from patients with HCV-RNA-positive chronic hepatitis C. Patients and Methods: A total of 10 patients with chronic hepatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…found that hemodialysis, hemofiltration and peritoneal dialysis in chronic dialysis patients infected with HCV produced significantly lower HCV‐RNA levels in the blood 12 . There are reports of combined granulocyte apheresis with IFN therapy for chronic hepatitis C, 13–15 and also reports claiming that early reduction of the virus is important in the treatment of chronic hepatitis C 16,17 . Thus, the potential effectiveness of IFN therapy combined with early virus removal by a physical method is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that hemodialysis, hemofiltration and peritoneal dialysis in chronic dialysis patients infected with HCV produced significantly lower HCV‐RNA levels in the blood 12 . There are reports of combined granulocyte apheresis with IFN therapy for chronic hepatitis C, 13–15 and also reports claiming that early reduction of the virus is important in the treatment of chronic hepatitis C 16,17 . Thus, the potential effectiveness of IFN therapy combined with early virus removal by a physical method is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…11 Ishida et al found that hemodialysis, hemofiltration and peritoneal dialysis in chronic dialysis patients infected with HCV produced significantly lower HCV-RNA levels in the blood. 12 There are reports of combined granulocyte apheresis with IFN therapy for chronic hepatitis C, [13][14][15] and also reports claiming that early reduction of the virus is important in the treatment of chronic hepatitis C. 16,17 Thus, the potential effectiveness of IFN therapy combined with early virus removal by a physical method is of particular interest. Moreover, Sakai et al reported the mechanism of clinical results by plasmapheresis whereby HCV in the blood was related to the treatment effects of IFN therapy, which could be enhanced by removing the virus from the blood.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodialysis, hemofiltration and peritoneal dialysis in chronic dialysis patients infected with HCV significantly lower HCV RNA levels in the blood [16] . Combined granulocyte apheresis with IFN therapy for CHC [17][18][19] and the prerequisite for early reduction of the virus in the treatment of CHC [20,21] are essential. Thus, the potential effectiveness of IFN therapy combined with early physical removal of the virus is of particular interest.…”
Section: Discussionmentioning
confidence: 99%